2018
DOI: 10.1002/brb3.1062
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of restless legs syndrome plasmatic biomarkers by proteomic analysis

Abstract: ObjectivesRestless legs syndrome (RLS) can lead to severe clinical consequences, thus negatively impacts on patients’ overall health and quality of life. Nevertheless, the pathophysiology of RLS is still unclear, resulting in underestimate, incorrect, or ignored diagnosis and in limited management and treatment. The aim of this study was to compare the plasma proteome of RLS patients and healthy controls, in the search of diagnostic biomarkers related to the disease severity.Materials and MethodsTwo‐dimensiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 40 publications
2
18
1
Order By: Relevance
“…In line with the results of the proteomic analysis by Bellei et al, 33 in our study, the concentration of A 1 AT was substantial in RLS patients. A 1 AT has pleiotropic effects, having been shown an association with pathways of inflammation, memory disorders, pregnancy, and cardiovascular disease as well as activation of antioxidant enzymes, suppression of oxidation stress, and decrease apoptosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In line with the results of the proteomic analysis by Bellei et al, 33 in our study, the concentration of A 1 AT was substantial in RLS patients. A 1 AT has pleiotropic effects, having been shown an association with pathways of inflammation, memory disorders, pregnancy, and cardiovascular disease as well as activation of antioxidant enzymes, suppression of oxidation stress, and decrease apoptosis.…”
Section: Discussionsupporting
confidence: 93%
“… 74 This is prominently denoted in Figure 1A and D . In the study by Bellei et al, 33 Hp was characteristically found to be upregulated; The discrepant results may result from the inclusion in this study of RLS patients on medications, which might have affected the results of the proteomic analysis. In our study, the differential regulation of Hp might be also related to a chronic inflammatory milieu involved in the modulation of RLS.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Transcripts that were upregulated in the peri-infarcted area both by ES and lesion included genes of immunoglobulin heavy chain involved in B cells development which were knew to stroke and schizophrenia ( Pandey et al, 2018 ) but also genes involved in Ataxia telangiectasia [immunoglobulin J polypeptide (IgJ)] ( Castro and Flajnik, 2014 ; Steinel et al, 2014 ), Fc domain of Ig that binds to a cell surface receptor (Fcris) which is secreted by activated microglia in neurodegenerative diseases like Alzheimer‘ disease ( Bisht et al, 2018 ) as well as Ig kappa chain V–III region MOPC 6-like (LOC50284) involved in the Restless legs syndrome ( Bellei et al, 2018 ) ( Table 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Alpha-1B-glycoprotein is a secreted plasma protein and a member of the immunoglobulin superfamily with a reasonable role in the immune system and in cell adhesion. Bellei et al [35] revealed increased alpha-1B-glycoprotein by proteomic analysis of plasma samples of patients with restless leg syndrome. Biswas et al [36] have identified, by an immunoproteomic approach, a higher expression of alpha-1B-glycoprotein in synovial fluid of patients with rheumatoid arthritis, proposing this glycoprotein as a biomarker of diagnostic importance for rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%